Closed-loop schemes for position and sway control of a gantry crane system - Alhassan, A. (UK Simulation Society, 2016)
This paper presents the investigation into the performance of Lyapunov pole placement (LPP), linear quadratic regulator (LQR) and proportional-integral-derivative (PID) control schemes for payload sway control and trolley position tracking of a gantry crane system. A 2D gantry crane system is considered. The nonlinear model of the system is derived using the Lagrangian energy equation and then linearized using Taylor’s series expansion. To investigate the performances of the designed controllers, a unit step input as a reference perturbation is applied to the controllers. MATLAB simulation results of the responses are analysed in time domain. The response time specifications of the trolley position, level of payload sway reduction, and robustness to parameter variation and uncertainties are used to assess the performances of the controllers.